DAMPAK PANDEMI COVID-19: KARAKTERISTIK DEWAN DIREKSI DAN KOMITE AUDIT TERHADAP KINERJA PERUSAHAAN - Lenny Julyanti; Meiliana Suparman (Jurnal Ilmiah Akuntansi Peradaban, 2022)
This study aims to analyze the effect of Covid-19 pandemic on corporate governance and firm performance, and also examines the relationship between governance and performance when pandemic occurs. Governance consists of board of directors’ and audit committee’ characteristics. Performance is proxied by return on assets and equity (ROA and ROE). Research sample consists of 146 listed consumer goods companies in Indonesian Stock Exchange from 2018 to 2021. Paired sample t-test and panel regression were used to test hypotheses. Paired sample t-test shows the pandemic affects directors' size and independence, ROA, ROE, and DPS. There is an impact of pandemic on directors’ education, audit committees’ independence, and leverage on the ROA. Moreover, pandemic has an impact on the effect of directors’ size and audit committee’s independence on ROE.